A graphene oxide based smart drug delivery system for tumor mitochondria-targeting photodynamic therapy. Issue 6 (22nd January 2016) - Wei, Yanchun; Zhou, Feifan; Zhang, Da; Chen, Qun; Xing, Da
Abstract : A graphene oxide-based two-stage drug delivery system is presented for photodynamic therapy to sequentially target tumor cells and their mitochondria. The nanodrug is unactivated and turns on until it arrives at the cellular mitochondria. Abstract : Subcellular organelles play critical roles in cell survival. In this work, a novel photodynamic therapy (PDT) drug delivery and phototoxicity on/off nano-system based on graphene oxide (NGO) as the carrier is developed to implement subcellular targeting and attacking. To construct the nanodrug (PPa-NGO-mAb), NGO is modified with the integrin αv β3 monoclonal antibody (mAb) for tumor targeting. Pyropheophorbide-a (PPa) conjugated with polyethylene-glycol is used to cover the surface of the NGO to induce phototoxicity. Polyethylene-glycol phospholipid is loaded to enhance water solubility. The results show that the phototoxicity of PPa on NGO can be switched on and off in organic and aqueous environments, respectively. The PPa-NGO-mAb assembly is able to effectively target the αv β3 -positive tumor cells with surface ligand and receptor recognition; once endocytosized by the cells, they are observed escaping from lysosomes and subsequently transferring to the mitochondria. In the mitochondria, the 'on' state PPa-NGO-mAb performs its effective phototoxicity to kill cells. The biological and physical dual selections and on/off control of PPa-NGO-mAb significantly enhance mitochondria-mediated apoptosis of PDT. This smart system offers a potential alternative to drug delivery systems for cancer therapy.